Obesity and periodontal disease: why suggest such relationship? An overview - Beatriz de Brito Bezerra; Enilson Antônio Sallum; Antônio Wilson Sallum (Universidade Estadual de Campinas, 2016)
Obesity is a chronic condition that has social and economic implications for public health. It can be associated with periodontal disease since the metabolic alterations observed in that condition could have some influence in immunity. The elevated levels of lipid and glucose can be associated with periodontal disease, contributing to an exacerbated host inflammatory response, alterations in neutrophil function, and with the inhibition of macrophage growth factors, reducing tissuehealing capacity. In this way, obese individuals could have higher chances of undergoing tissue destruction in the presence of periodontal infection. On the other hand, periodontitis may be involved in alterations of lipid metabolism, since gram-negative bacteria could promote a rise in cholesterol and triglyceride levels due to chronic exposure to low levels of LPS in circulating blood, leading to the production of cytokines, which could initiate the production of lipoproteins by the liver. The objective was to review the literature about obesity and periodontal disease and provide a better understanding of their relationship.